Severe myositis of the hip flexors after pre-operative chemoradiation therapy for locally advanced rectal cancer: case report. Issue 1 (December 2016) - Florczynski, Matthew; Sanatani, Michael; Mai, Lauren; Fisher, Barbara; Moulin, Dwight; Cao, Jeffrey; Louie, Alexander; Pope, Janet; Leung, Eric
Abstract Background The use of neoadjuvant radiation therapy and chemotherapy in the treatment of locally advanced rectal adenocarcinoma has been shown to reduce disease recurrence when combined with surgery and adjuvant chemotherapy. We report a case of a patient who developed a debilitating bilateral myopathy of the hip flexors after successful treatment for rectal cancer. To the best of our knowledge, this is the first such complication from radiation therapy reported in a patient with colorectal cancer. The disproportionate severity of our patient's myopathy relative to the dose of radiation used also makes this case unique among reports of neuromuscular complications from radiation therapy. Case presentation The patient is a 65-year-old male with node negative, high-grade adenocarcinoma of the rectum penetrating through the distal rectal wall. He underwent neoadjuvant concurrent pelvic radiation therapy and capecitabine-based chemotherapy, followed by abdominoperineal resection and post-operative FOLFOX chemotherapy. Five months post-completion of pelvic radiotherapy and 2 months after the completion of adjuvant chemotherapy, he presented with bilateral weakness of the iliopsoas muscles and severe pain radiating to the groin. The patient improved with 40 mg/d of prednisone, which was gradually tapered to 2 mg/d over 6 months, with substantial recovery of muscle strength and elimination of pain. Conclusions The timing, presentation and response of our patient's symptoms to corticosteroids are most consistent with a radiation recall reaction. Radiation recall is a phenomenon whereby previously irradiated tissue becomes vulnerable to toxicity by subsequent systemic therapy and is rarely associated with myopathies. Radiation recall should be considered a potential complication of neoadjuvant radiation therapy for rectal cancer, and for ongoing research into the optimization of treatment for these patients. Severe myopathies caused by radiation recall may be fully reversible with corticosteroid treatment.